(untitled) - Ochsenwald, William (Boston, Mass., 2004)
Praised for its straightforward and accessible style, this text provides a general introduction to the chief elements in Middle Eastern history, allowing readers to proceed into more specialized topics and themes with a solid understanding of the most current scholarship in the field.
Keywords: Middle East,Trung Đông; History,Lịch sử